Catalysing scientific research with AI: unlocking new frontiers through generative AI - Siti Hasnah Tanalol; Asni Tahir; Salmah Fattah; Azali Saudi (Pusat e-pembelajaran, UMS, 2023)
In today's rapidly evolving scientific landscape, the integration of Artificial Intelligence (AI) offers exceptional opportunities. This paper delves into the role of AI in advancing scientific research, with a particular focus on the transformative potential of Generative AI. By leveraging Generative AI's capabilities, researchers can expand the boundaries of knowledge, redefine experimental approaches, improve data analysis, generate hypothesis generation, and innovatively address complex challenges. We provide a concise summary of key topics, including the applications of Generative AI in scientific literature review, knowledge synthesis, and the optimization of experimental parameters. This paper emphasises core concepts of Generative AI, real-world case studies, and the ethical considerations associated with this technological advancement. Furthermore, we present insights from a survey involving 35 participants, which shed light on their awareness, attitudes, and expectations regarding Generative AI. By responsibly embracing Generative AI and integrating it with human expertise, researchers can leverage its power to accelerate scientific advancements and unlock new horizons of discovery. This paper aims to inspire researchers to explore the untapped potential of AI, in their scientific pursuits, propelling scientific research into new frontiers.